An investigation into the development of English language reading comprehension among Thai undergraduate students using an online blended learning approach - Chomchaiya, Chayapon (Curtin University, 2014)
This study investigated the use of a blended learning approach to the teaching of English reading comprehension in a Thai university. The study revealed while Thai learners experienced many difficulties with developing their reading comprehension, the blended learning program assisted in reducing the difficulties they experienced. The study also revealed that participants not only made significantly higher progress in the blended learning program but also enhanced their capacity for autonomous learning.